PENGUATAN DAN PERAN ORGANISASI KEMASYARAKATAN NGO ATAU NON-GOVERNMENTAL ORGANIZATION DALAM MEMBANGUN KEMITRAAN PENGABDIAN BERSAMA NAFIS FOUNDATION - Nasuhi; Mufidah; Hapipi Jayadi; Reni Anggriani; Didin Hadi Saputra; Masdani (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2021)
Indonesia is the largest archipelagic country in the world, and is also a developing country, which of course has many aspects on all fronts and on all sides. The problems in developing countries are of course the concern of all parties, especially the government which is currently the leader in leading the wheels of government. In overcoming these problems, of course, it must be handled in a good way or method, especially with a social approach or method, a preventive way, and a persuasive way. With the existence of these problems, of course, will have an adverse impact, both in terms of